2021
DOI: 10.1186/s12985-021-01610-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of ocular surface in a Covid -19 patient after Favipiravir treatment: a case report

Abstract: Background Favipiravir is used in treatment of Covid-19 patients. We aimed to share of ocular surface fluorescence in a patient after Favipiravir treatment in this case report. Case presentation A 20-year-old male patient declared no known systemic disease prior to Covid-19. He applied to us with blurry vision and blue light reflection after Covid-19 treatment with Favipiravir. We observed bilateral fluorescence on his eyes and fluorescence of his … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Studies have shown that the active phosphorylated metabolite of favipiravir is found in human plasma and that there is a linear correlation between its concentration and the intensity of fluorescence ( 16 ). In subsequent laboratory investigations ( 15 ), fluorescence characteristics of favipiravir tablet were examined under ultraviolet light, and the observations confirmed the fluorescence of the drug, which signified a robust association between the fluorescence of the ocular surface and favipiravir. Additionally, a direct relationship was found between the concentration of favipiravir and fluorescence intensity within a specific range (40–280 ng/ml).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Studies have shown that the active phosphorylated metabolite of favipiravir is found in human plasma and that there is a linear correlation between its concentration and the intensity of fluorescence ( 16 ). In subsequent laboratory investigations ( 15 ), fluorescence characteristics of favipiravir tablet were examined under ultraviolet light, and the observations confirmed the fluorescence of the drug, which signified a robust association between the fluorescence of the ocular surface and favipiravir. Additionally, a direct relationship was found between the concentration of favipiravir and fluorescence intensity within a specific range (40–280 ng/ml).…”
Section: Discussionmentioning
confidence: 77%
“…Mild hyperuricemia, diarrhea, and neutropenia were the most frequently reported side effects and accounted for 20% of all adverse events ( 9 ). Furthermore, several rare adverse effects have been documented, including the bluish discoloration of the cornea ( 10 ), temporary visual blurring ( 15 ), and fluorescence of the ocular surface ( 15 ). However, these adverse reactions were observed to have resolved after discontinuation of the medication, as reported by Raiturcar et al who documented the restoration of normal corneal color within a day ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doran et al 12 reported on a patient with whole ocular surface fluorescence liable to favipiravir intake. Their patient was a photographer and detected the fluorescence phenomenon by himself.…”
Section: Ocularmentioning
confidence: 99%
“…[ 3 ] Recently in April 2021 Doran et al . [ 4 ] reported a case where a 20-year-old photographer who was started on favipiravir presented on the second day of therapy with blurred vision and blue light reflection when he was exposed to UV light sources at his workplace. On examination, they noticed fluorescence of his corneas and nails under Wood’s lamp, but no bluish discoloration of cornea was noted and slit-lamp biomicroscopy was not significant.…”
mentioning
confidence: 99%